Pattern reconfigurable metamaterial antenna for 5G base station network - Esmail, Bashar Ali Farea (2021)
Reconfiguration of an antenna’s radiation pattern in a predefined direction is very important for enhancing the performance of communication systems in terms of the quality of service, system security, avoiding interference, and economizing power. Metamaterials, on the other hand, are commonly used in antenna design to enhance the gain, bandwidth, and efficiency and recently to tilt the radiation beam. Nonetheless, few issues had been encountered especially when the frequency is pushed to higher range such as the inherent losses that restrict the variety of their applications. Hence, metamaterials structures with relatively low loss are in high demand. In this thesis, various metamaterial structures with low loss properties are proposed. Then these structures are reconfigured and integrated with the fifth-generation (5G) planar antennas at two different frequency bands i.e. millimetre-wave (MMW) band and sub-6 GHz band for beam deflection applications. The modified double square ring resonator (DSRR) and contiguous squares resonator (CSR) structures are investigated numerically and experimentally to provide low loss property at 76 GHz and around 28 GHz, respectively. DSRR and CSR achieve losses of 0.5 dB and 0.2 dB, respectively. Both structures are manufactured and measured to validate the results. Furthermore, the analytical model is introduced to predict the electromagnetic behaviour of the proposed metamaterial structures. Thereafter, the CSR, Bridge shaped resonator (BSR) and split square resonator (SSR) structures are electronically reconfigured to produce different refractive indices at MMW and sub-6 GHz spectrums, which are used for deflecting the radiation beam of the 5G planar antennas. An array of unreconfigurable adjacent square-shaped resonators (ASSRs) has been also used for tilting the radiation pattern of planar antenna at sub-6 GHz spectrum. These proposed structures are included in the substrate of the dipole antenna and bow-tie antenna for deflecting the radiation pattern in E-plane at two different 5G bands of 28 GHz and 3.5 GHz. The results of all designs at both bands show that the radiation beam of the antennas is deflected in both positive and negative directions with respect to y-direction of antenna. At 28 GHz, a high deflection angle of 34° is obtained using simple structure, BSR, with gain improvement up to 1.9 dB (26.7%). On the other hand, at 3.5 GHz, the beam deflection angle of ±39º is achieved with gain enhancement up to 2.4 dB (35.6%) using passive beam deflection antenna whereas the beam deflection of ±36º is obtained using an active beam deflection antenna. The reconfigurable metamaterial antennas are proposed to be used in 5G base station network with advantages of high deflection angles, gain enhancement, low profile structure, low cost, lightweight, and easy integration with other circuits for 5G beam deflection applications.